Kebudayaan dan Kearifan Lokal Suku Dayak, Banjar, dan Jawa - Sugiyanto, Febri; Fajriyanur, Ivan; Ahmadi, Ahmadi; Ajhari, Ajhari (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study discusses the culture and local wisdom of three major ethnic groups in Indonesia: the Dayak, Banjar, and Javanese. Each group possesses a unique cultural heritage, including traditional houses, traditional arts, and customary ceremonies. Moreover, the local wisdom of each ethnic group reflects a close relationship between the community and the environment, social values, and spirituality. The aim of this study is to identify and analyze the cultural characteristics and local wisdom of these three ethnic groups. The research method used is a literature review and in-depth interviews with traditional leaders and cultural practitioners. The findings indicate that culture and local wisdom play a crucial role in preserving the identity and sustainability of indigenous communities amid changing times.